Near-infrared response antibacterial nano material as well as preparation method and application thereof
By encapsulating CuO2 nanoparticles and ICG in phase change material PCM, the near-infrared response antibacterial nanomaterial ICG/CuO2@PCM prepared, the problem of insufficient H2O2 and O2 in the skin-infected microenvironment is solved, and efficient antibacterial and good biocompatibility is achieved for a variety of bacteria.
Patent Information
- Application Number
- CN202411700464.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing antibacterial materials are insufficient in the skin-infected microenvironment, resulting in reduced antibacterial efficiency, and unstable metal peroxides, easy to decompose, and strong toxic side effects, limiting their application in the field of biomedical science.
A near-infrared-responsive antibacterial nanomaterial ICG/CuO2@PCM was prepared, and the synergy between chemodynamic therapy, photodynamic therapy and photothermal therapy that self-supplied hydrogen peroxide and oxygen was achieved by encapsulating CuO2 nanoparticles and indocyanine green (ICG) in the phase change material PCM.
The broad-spectrum antibacterial to Staphylococcus aureus and MRSA was achieved, with a bacteriostatic rate of 99.9%, overcoming the limitations of lack of H2O2 and O2 in the bacterial infection environment, improving the bactericidal effect, and having good biocompatibility.
Smart Images

Figure CN119700706A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antibacterial materials, and in particular to a near-infrared responsive antibacterial nano material and a preparation method and application thereof. Background Art
[0002] Bacteria can cause many types of skin and soft tissue infections and are one of the biggest enemies of human health today. Current treatment methods mainly use large doses of antibiotics to fight bacterial infections, but the rapid generation and evolution of bacterial resistance makes clinical infection treatment difficult.
[0003] In recent years, antimicrobial strategies based on the generation of reactive oxygen species (ROS) by chemodynamic therapy (CDT) and photodynamic therapy (PDT) have attracted wide attention. However, the lack of H2O2 and O2 in the microenvironment of skin infection seriously reduces their antimicrobial efficiency. Metal peroxides can react with H2O to generate H2O2, which can decompose to generate O2 under heating conditions. However, the instability, easy decomposition, and strong toxic side effects of metal peroxides have greatly limited their application in the biomedical field.
[0004] In the literature (Self-enhanced ROS generation by responsive co-delivery of H2O2and O2 based on a versatile composite biomaterial for hypoxia-irrelevantmultimodal antibiofilm therapy, Jiayu Xiao et al., Chemical Engineering Journal, Volume 465, 1June 2023, 142958), CuO2 and ICG were loaded onto the surface of polydopamine (PDA) particles to obtain PDA / CP / ICG. The drug loading rate of CuO2 in PDA / CP / ICG was only 41.5%, which was low. When the concentration of PDA / CP / ICG was above 100 μg / mL, the irradiation time of near-infrared light source was 10 minutes in antibacterial applications. The irradiation time was long, and long-term near-infrared irradiation may cause overheating of nanoparticles, resulting in damage to surrounding tissues. Later clinical applications will also cause discomfort to patients, affecting treatment compliance. Summary of the invention
[0005] The present invention proposes a near-infrared responsive antibacterial nanomaterial and a preparation method and application thereof. The prepared ICG / CuO2@PCM has good antibacterial properties, no drug resistance and stability, and realizes the combined antibacterial effects of three modes: CDT / PDT / PTT, and has broad-spectrum antibacterial properties and good biocompatibility.
[0006] The technical solution of the present invention is implemented as follows: a near-infrared responsive antibacterial nanomaterial, the near-infrared responsive antibacterial nanomaterial (ICG / CuO2@PCM) has CuO2 nanoparticles and indocyanine green (ICG) as the core and phase change material PCM as the shell.
[0007] Furthermore, the particle size of the CuO2 nanoparticles is 5-20 nm, and the particle size of the near-infrared responsive antibacterial nanomaterials is 100-350 nm.
[0008] Furthermore, the melting point of the phase change material PCM is 40-45°C.
[0009] Furthermore, the phase change material PCM is prepared by esterification reaction of hexadecanol and oleic acid.
[0010] Furthermore, the loading amount of CuO2 nanoparticles is 60%-90%.
[0011] A method for preparing a near-infrared responsive antibacterial nanomaterial comprises the following steps:
[0012] 1) mixing cupric chloride dihydrate and hydrogen peroxide under alkaline conditions for reaction, and performing ultrafiltration to obtain CuO2 nanoparticles;
[0013] 2) dispersing hexadecanol and oleic acid in ethanol, ultrasonically treating, and vacuum drying to obtain a phase change material PCM;
[0014] 3) CuO2 nanoparticles, ICG and a surface modifier are mixed as solution 1, and the phase change material PCM is dissolved in ethanol as solution 2. Solution 1 and solution 2 are mixed, ultrasonically treated, and then immediately placed in an ice bath. After the ice bath, dialyzed to obtain a near-infrared responsive antibacterial nanomaterial.
[0015] Furthermore, in step 1), the mixing reaction time is 30-60 min, the temperature is 20-30° C., and a 50 kD ultrafiltration tube is used for centrifugation at a speed of 5000-7000 rpm.
[0016] Furthermore, in step 2), the mass ratio of oleic acid to hexadecanol is 1:2-5, the ultrasonic treatment is performed for 5-20 minutes, and the vacuum drying temperature is 40-60°C.
[0017] Furthermore, in step 3), in solution 1, the concentration of CuO2 nanoparticles is 1-5 mg / mL, the concentration of ICG is 0.1-5 mg / mL, the surface modifiers are lecithin and DSPE-mPEG, the concentration of lecithin is 1-10 mg / mL, and the concentration of DSPE-mPEG is 0.5-10 mg / mL; in solution 2, the concentration of phase change material PCM is 5-20 mg / mL; the volume ratio of solution 1 and solution 2 is 10:0.5-1.
[0018] Furthermore, in step 3), the ultrasonic temperature is 42-50° C., the ultrasonic time is 5-20 min, the ice water bath time is 5-20 min, the dialysis bag molecular weight cutoff is 8-20 kD, and the dialysis time is 24-48 h.
[0019] Application of near-infrared responsive antibacterial nanomaterial in the preparation of antibacterial drugs.
[0020] Beneficial effects of the present invention:
[0021] The ICG / CuO2@PCM nano antibacterial material prepared by the present invention has enhanced photostability of ICG under the protection of PCM; through the synergistic effect of CuO2 and ICG, the antibacterial rate of ICG / CuO2@PCM against Staphylococcus aureus and MRSA reaches 99.9%, which indirectly indicates that the drug resistance of MRSA to ICG / CuO2@PCM is ineffective, which is significantly higher than 77.4% of ICG@PCM; and the drug loading rate of CuO2 in the ICG / CuO2@PCM nanoparticles prepared by the present invention can reach more than 87%, and when the concentration of ICG / CuO2@PCM nanoparticles is above 100 μg / mL, the irradiation time using a near-infrared light source is only 5 minutes.
[0022] The ICG / CuO2@PCM nano antibacterial material prepared by the present invention realizes the synergy of chemodynamic therapy, photodynamic therapy and photothermal therapy with self-supply of hydrogen peroxide and oxygen, overcomes the limitation of lack of H2O2 and O2 in the bacterial infection environment, improves the bactericidal effect, and requires a low concentration for antibacterial effect. At the same time, it has good biocompatibility and a broad-spectrum bactericidal effect.
[0023] The ICG / CuO2@PCM nano antibacterial material of the present invention is prepared by encapsulating CuO2 and ICG in an organic phase change material PCM. The preparation method is simple and efficient, the reaction conditions are mild, the cost is low, and it is suitable for large-scale industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 It is a comparison chart of the stability of ICG / CuO2@PCM and ICG;
[0026] Figure 2 This is the transmission electron microscope image of CuO2;
[0027] Figure 3 is the SEM image of ICG / CuO2@PCM;
[0028] Figure 4 is the UV spectrum of ICG / CuO2@PCM;
[0029] Figure 5 is the XPS spectrum of ICG / CuO2@PCM;
[0030] Figure 6 is the photothermal performance diagram of ICG / CuO2@PCM;
[0031] Figure 7 is the chemodynamic therapy performance diagram of ICG / CuO2@PCM;
[0032] Figure 8 It is the amount of OH generated by CuO2 under heating and unheating conditions;
[0033] Fig. 9 is the photodynamic therapy performance diagram of ICG / CuO2@PCM;
[0034] Fig.10 is the antibacterial performance graph of ICG / CuO2@PCM against various bacteria;
[0035] Fig.11 is the antibacterial performance graph of ICG / CuO2@PCM and different materials against various bacteria;
[0036] Fig.12 It is the result of the biocompatibility of ICG / CuO2@PCM to various cells;
[0037] Fig.13 This is the scanning electron microscopy image of ICG / CuO2@PCM with a CuO2 concentration of 2 mg / mL. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing a near-infrared responsive antibacterial nanomaterial comprises the following steps:
[0041] 1) Synthesis of CuO2 nanoparticles: PVP (2.5 g) was dissolved in CuCl2·2H2O (25 mL, 0.01 M) aqueous solution, and then NaOH (25 mL, 0.02 M) and 30% H2O2 (500 μL) were added in sequence. After stirring at 25°C for 30 min, the CuO2 nanoparticles were collected by ultrafiltration and washed with water three times.
[0042] 2) Synthesis of PCM: 40 mg of oleic acid and 100 mg of 1-hexadecanol were added to 10 ml of anhydrous ethanol, and after 5 min of ultrasonic treatment, the mixture was vacuum dried at 40 °C for 6 h.
[0043] 3) Synthesis of ICG / CuO2@PCM: 9 mg of phase change material PCM was dissolved in 0.5 mL of ethanol to obtain solution 2; 10 mL of 4% ethanol aqueous solution was used as solvent, CuO2 nanoparticles were added, and the concentration of CuO2 nanoparticles was 1 mg / mL, and then 5 mg of DSPE-mPEG-2000, 20 mg of lecithin and 3 mg of ICG were added to obtain solution 1, and solution 1 was added to solution 2, heated under ultrasound at 48°C for 5 min, immediately placed in an ice bath, ice bathed for 10 min, and dialyzed in DI water for 24 h. The drug loading rate of CuO2 in the ICG / CuO2@PCM nanoparticles prepared in this embodiment can reach 87.27%.
[0044] Example 2
[0045] A method for preparing a near-infrared responsive antibacterial nanomaterial comprises the following steps:
[0046] 1) Synthesis of CuO2 nanoparticles: PVP (2.5 g) was dissolved in CuCl2·2H2O (25 mL, 0.01 M) aqueous solution, and then NaOH (25 mL, 0.02 M) and 30% H2O2 (500 μL) were added in sequence. After stirring at 25°C for 30 min, the CuO2 nanoparticles were collected by ultrafiltration and washed with water three times.
[0047] 2) Synthesis of PCM: 40 mg of oleic acid and 160 mg of 1-hexadecanol were added to 10 ml of anhydrous ethanol. After 5 minutes of ultrasonic treatment, the mixture was vacuum dried at 40 °C for 5 hours.
[0048] 3) Synthesis of ICG / CuO2@PCM: 18 mg PCM was dissolved in 1 mL ethanol to obtain solution 2; 10 mL of 4% ethanol aqueous solution was used as solvent, CuO2 nanoparticles were added, and the concentration of CuO2 nanoparticles was 1 mg / mL, and then 10 mg DSPE-mPEG-2000, 20 mg lecithin and 10 mg ICG were added to obtain solution 1, solution 1 was added to solution 2, heated at 48°C under ultrasound for 5 min, immediately placed in an ice bath, ice bath for 10 min, and dialyzed in DI water for 24 h.
[0049] Comparison of the stability of ICG / CuO2@PCM prepared in Example 1 and free ICG Figure 1 As shown by Figure 1 It can be seen that when ICG is encapsulated in the phase change material PCM, ICG can be unaffected by external water and oxygen, effectively reducing photodegradation and improving its photostability.
[0050] 1. Electron microscopy images of CuO2 nanoparticles and ICG / CuO2@PCM nanoparticles
[0051] The CuO2 nanoparticles prepared in Example 1 and the transmission electron microscope image are as follows Figure 2 As shown by Figure 2 It can be seen that the prepared CuO2 nanoparticles have a uniform particle size of about 10 nm.
[0052] The scanning electron microscopy image of ICG / CuO2@PCM prepared in Example 1 is as follows Figure 3 (Bar=200nm) Figure 3 It can be seen that ICG / CuO2@PCM is evenly distributed, regular in shape, and has a particle size of about 120nm (left picture). However, under laser irradiation, ICG / CuO2@PCM begins to melt, resulting in a gradually irregular shape and a reduced particle size (right picture).
[0053] 2. UV and XPS spectra of ICG / CuO2@PCM nanoparticles
[0054] The CuO2 nanoparticles and ICG / CuO2@PCM nanoparticles were dispersed in distilled water, ultrasonically dispersed, and the spectra at 300-900 nm were measured using an ultraviolet spectrophotometer. Figure 4As shown, the UV-visible absorption spectrum shows that ICG is loaded successfully, and the characteristic absorption peak of ICG is red-shifted from 780 nm to 800 nm, which may be due to the enrichment of ICG, but is more conducive to the excitation of nanoparticles at 808 nm.
[0055] XPS spectra of ICG / CuO2@PCM nanoparticles are shown in Figure 5 As shown, the characteristics of C, N, Cu, O and S elements are displayed. The Cu 2p peak indicates that CuO2 is successfully loaded, while the N1s peak indicates the presence of PVP coating on the CuO2 surface. The appearance of the S2p peak confirms that ICG is successfully loaded.
[0056] 3. Photothermal performance test of ICG / CuO2@PCM nanoparticles
[0057] ICG / CuO2@PCM was dispersed in deionized water to form dispersions of different concentrations. 1 mL was taken into an EP tube and irradiated with an 808 nm laser (1 W / cm 2 ) for 5 minutes (NIR), and use an electronic thermometer to measure and record the temperature every half minute. Figure 6 As shown, the dispersion with a drug concentration of 0 as a control had no obvious photothermal effect, and the temperature did not rise significantly after 5 minutes of illumination. The temperature of the dispersion with a concentration of 200 μg / mL increased from 23.5°C to 55.6°C after 5 minutes of illumination. This temperature is enough to reach the melting point of PCM, thereby prompting it to release its contents, and can also play a role in photothermal sterilization.
[0058] 4. Chemodynamic therapy performance test of ICG / CuO2@PCM
[0059] ICG / CuO2@PCM can decompose under weak acidic conditions to produce hydrogen peroxide and Cu 2+ , followed by hydrogen peroxide and Cu 2+ The Fenton-like reaction generates hydroxyl radical ·OH, which can react with 3,3',5,5'-tetramethylbenzidine (TMB) to generate TMB oxide. The TMB oxide product has a characteristic peak at 652nm. The absorbance at 652nm was measured using an ELISA instrument to evaluate its chemodynamic therapy performance. In pH 5.5 buffer, 200μg / mL of ICG / CuO2@PCM was mixed with TMB (200μg / mL), and water was used as a control to measure its absorbance at 652nm. The results are shown in Figure 2. Figure 7As shown in the figure (+INR, referring to 808 near-infrared irradiation for 5 minutes), the color of the Control group (control group, ultrapure water) did not change, and the UV-visible absorption peak of TMB at 652nm did not change significantly when the pH was 7.4. However, under near-infrared irradiation at pH 5.5, the peak at 652nm increased significantly compared with the control group (ultrapure water), indicating that ICG / CuO2@PCM can release CuO2 in response to 808nm near-infrared irradiation, and then CuO2 undergoes a Fenton-like reaction in an acidic microenvironment (pH 5.5) to generate ·OH.
[0060] The amount of OH generated by the CuO2 nanoparticles prepared in Example 1 under heating and non-heating conditions is as follows: Figure 8 As shown by Figure 8 It can be seen that under heating conditions, the amount of ·OH produced by CuO2 increases significantly, indicating that the photothermal effect of ICG in this system can improve the CDT efficiency of CuO2, thereby increasing the yield of ·OH.
[0061] 5. Photodynamic therapy performance test of ICG / CuO2@PCM nanoparticles
[0062] ICG / CuO2@PCM can generate singlet oxygen under near-infrared irradiation at 808 nm 1 O2, once 1 O2 combines with DPBF, DPBF will be irreversibly oxidized, and the absorbance at UV-visible light will decrease rapidly. Different materials (200 μg / mL) were mixed with DPBF (40 μg / mL) and then irradiated with 808 nm near-infrared laser (1 W / cm 2 The absorbance at 417 nm was measured at 50 °C for 5 min (abbreviated as INR). Fig. 9 As shown in Figure 2, the absorbance of the control group (ultrapure water), CuO2@PCM group and ICG / CuO2@PCM group was almost unchanged. However, the absorbance at 410 nm of the ICG@PCM+NIR group and ICG / CuO2@PCM+NIR group decreased significantly with the increase of irradiation time, which indicates that 1 O2 production is generated by ICG after NIR irradiation. It is worth noting that the ICG / CuO2@PCM+NIR group produces 1 The O2 content in the CuO2-treated group was significantly higher than that in the ICG@PCM+NIR group. This enhancement is due to the fact that under heating conditions, CuO2 can provide more O2 for PDT, thereby improving the efficiency of PDT.
[0063] 6. Antibacterial properties of ICG / CuO2@PCM nanoparticles at different concentrations
[0064] Gram-positive Staphylococcus aureus (S. aureus), Gram-negative Escherichia coli (E. coli) and methicillin-resistant Staphylococcus aureus (MRSA) were selected as model strains. Different concentrations of drugs were mixed with fresh bacterial suspension (1×10 6 CFU / mL). The mixture was then divided into two groups: with and without laser irradiation (1 W / cm 2 , 5min). Take 100μL of the treated suspension from each group and spread it evenly on the agar plate. After culturing in a 37℃ constant temperature incubator for 16h, count the number of colonies on the agar plate. The results are as follows Fig.10 As shown in the figure, at the same concentration, the colony count of the near-infrared treatment group was significantly lower than that of the non-near-infrared treatment group, indicating that ICG / CuO2@PCM only exhibits antibacterial properties under near-infrared response. In addition, with the increase of ICG / CuO2@PCM concentration, the number of bacterial colonies decreased significantly. At a concentration of 100μg / mL, the inhibition rate of ICG / CuO2@PCM against Staphylococcus aureus and MRSA reached 99.9%, indirectly indicating that MRSA's resistance to ICG / CuO2@PCM is ineffective. At the same time, for E. coli, the concentration of ICG / CuO2@PCM needs to be increased to 125μg / mL to achieve a similar inhibition rate, which may be related to the complex cell wall composition of E. coli.
[0065] The antibacterial properties of ICG / CuO2@PCM prepared in Example 1 and different materials against various bacteria are shown in Figure 2. Fig.11 As shown in the figure, the antibacterial activity of CuO2@PCM is low. In contrast, the bactericidal effect of ICG / CuO2@PCM reaches 99.9%, which is significantly higher than 77.4% of ICG@PCM. This further proves that CuO2 can supply O2 to improve the PDT efficiency of ICG, thereby playing a synergistic bactericidal role.
[0066] 7. Biocompatibility of ICG / CuO2@PCM nanoparticles on various cells
[0067] The CCK-8 method was used to evaluate the cytotoxicity of ICG / CuO2@PCM on mouse embryonic fibroblasts (NIH-3T3), human umbilical vein endothelial cells (HUVEC) and cervical cancer cells (Hela). The cells were seeded into 96-well cells (1×10 5 Cells were incubated at 37°C in a 5% CO2 incubator for 24 h and treated with different concentrations of ICG / CuO2@PCM for 24 and 72 h. After treatment, the cells were washed three times with sterile PBS and fresh culture medium containing CCK8 reagent (100 μL) was added each time. The cells were incubated at 37°C for 4 h and the absorbance at 495 nm was measured for each well. The results are shown in Figure 2. Fig.12As shown in the figure, when the concentration of ICG / CuO2@PCM reached 150 μg / mL, the survival rate of the three cells remained above 80%. The results showed that ICG / CuO2@PCM has good biocompatibility.
[0068] In summary, the ICG / CuO2@PCM nanoparticles prepared by the present invention have excellent antibacterial properties, good safety, high biocompatibility, low required concentration, and spectral bactericidal effects, and can be used to prepare antibacterial drugs.
[0069] Since CuO2 plays a "core" role in ICG / CuO2@PCM, in step 3), when the CuO2 concentration is lower than 1 mg / mL, such as 0.5 mg / mL, the CuO2, ICG and PCM cannot be formed after mixing. When the CuO2 concentration is higher than 1 mg / mL, such as 2 mg / mL, the ICG / CuO2@PCM has irregular shapes and different sizes (such as Fig.13 shown).
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A near-infrared responsive antibacterial nanomaterial, characterized in that: The near-infrared responsive antibacterial nanomaterials have CuO2 nanoparticles and ICG as the core and phase change material PCM as the shell.
2. The near-infrared responsive antibacterial nanomaterial according to claim 1, characterized in that: The particle size of the CuO2 nanoparticles is 5-20nm, the particle size of the near-infrared responsive antibacterial nanomaterials is 100-350nm; and the loading amount of the CuO2 nanoparticles is 60%-90%.
3. The near-infrared responsive antibacterial nanomaterial according to claim 1, characterized in that: The melting point of phase change material PCM is 40-45°C.
4. A near-infrared responsive antibacterial nanomaterial according to claim 1 or 3, characterized in that: Phase change material PCM is prepared by esterification reaction of hexadecanol and oleic acid.
5. The method for preparing a near-infrared responsive antibacterial nanomaterial according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) mixing cupric chloride dihydrate and hydrogen peroxide under alkaline conditions for reaction, and performing ultrafiltration to obtain CuO2 nanoparticles; 2) dispersing hexadecanol and oleic acid in ethanol, ultrasonically treating, and vacuum drying to obtain a phase change material PCM; 3) CuO2 nanoparticles, ICG and a surface modifier are mixed as solution 1, and the phase change material PCM is dissolved in ethanol as solution 2. Solution 1 and solution 2 are mixed, ultrasonically treated, and then immediately placed in an ice bath. After the ice bath, dialyzed to obtain a near-infrared responsive antibacterial nanomaterial.
6. The preparation method according to claim 5, characterized in that: In step 1), the mixing reaction time is 30-60 minutes and the temperature is 20-30°C.
7. The preparation method according to claim 5, characterized in that: In step 2), the mass ratio of oleic acid to hexadecanol is 1:2-5, and the ultrasonic treatment is performed for 5-20 minutes.
8. The preparation method according to claim 5, characterized in that: In step 3), in solution 1, the concentration of CuO2 nanoparticles is 1-5 mg / mL, the concentration of ICG is 0.1-5 mg / mL, the surface modifiers are lecithin and DSPE-mPEG, the concentration of lecithin is 1-10 mg / mL, and the concentration of DSPE-mPEG is 0.5-10 mg / mL; in solution 2, the concentration of phase change material PCM is 5-20 mg / mL; the volume ratio of solution 1 to solution 2 is 10:0.5-1.
9. The preparation method according to claim 5 or 8, characterized in that: In step 3), the ultrasonic temperature is 42-50° C., the ultrasonic time is 5-20 min, and the ice water bath time is 5-20 min.
10. Use of a near-infrared responsive antibacterial nanomaterial according to any one of claims 1 to 4 in the preparation of antibacterial drugs.
Citation Information
Patent Citations
Near-infrared light response nanoparticle and controlled release system
CN111671914A
Metal organic framework coated nano-particles capable of automatically supplying H2O2 / O2 and consuming GSH as well as preparation method and application of metal organic framework coated nano-particles
CN114848813A
Preparation method of antibacterial photoresponse composite material
CN115414478A
Photo-thermal-chemical power nano antibacterial agent and preparation method and application thereof
CN116327929A
PH (potential of hydrogen) and ATP (adenosine triphosphate) dual-responsive nano antibacterial agent as well as preparation method and application thereof
CN117482232A